Quality of life among morbid obese and patients submitted to bariatric surgery - Lívia Moreira Barros; Rosa Aparecida Nogueira Moreira; Natasha Marques Frota; Thiago Moura de Araújo; Joselany Áfio Caetano (Universidade Federal de Goias, 2015)
The objective was to assess Quality of Life (QoL) among obese waiting for bariatric surgery and post-surgery patients. A cross-sectional quantitative study conducted in a hospital reference in bariatric surgery in Fortaleza-CE. The sample was composed by 64 pre- and 92 post-surgery patients. Data was collected through the QoL questionnaire Moorehead-Ardelt II from the Bariatric Analysis and Reporting Outcome System (BAROS) protocol. Most individuals at pre-surgery stage classified their QoL as minimal - 57,8% (37), while the post-surgery group observed a significant change where 75% (69) of participants considered their QoL very good after the procedure (p< 0,001). In both groups, the QoL aspects that presented worse evaluation were: physical activity, sexual interest and eating behavior. Bariatric surgery represents improvement in quality of life of individuals.